ESTIMATION OF HERITABILITY COEFICIENTS FOR PREGNANCY LENGTH AND CALF BIRTH WEIGHT IN THE POPULATION OF HOLSTEIN CATTLE IN THE REPUBLIC OF SERBIA - Stanojevic, Dragan Ž. (Journal of Agricultural Sciences (Belgrade), 2025)
The duration of pregnancy in cows and the body weight of calves at birth have a great influence on the flow and weight of the particle in dairy cows, and thus a very significant impact on the economy of cattle production. The aim of the study was to determine the phenotypic variability and heredity of these traits and the possibility of selection for these traits in the dairy cattle population in the Republic of Serbia. The research included 1348 Holstein Friesian cows that were calved 4247 times in the period from 2007 to 2016 on a farm near Belgrade. The examination of the significance of the factors was done within the GLM procedure of the SAS statistical package. Components of variance were calculated using the REML methodology within the VARCOMP procedure of the SAS statistical package (see 9.4). The average duration of pregnancy in the examined population was 278.5 days, while the average body weight of calves at birth was 37.1 kg. The study found high statistical significance of lactation, year and calving season as well as half of calves on both examined traits, except in the case of calving season on calf body weight, where the season had a statistically significant impact. The duration of pregnancy had a low heredity of 0.018, while the established heredity of birth weight was 0.355.